Statius and epic games : sport, politics, and poetics in the Thebaid - Lovatt, Helen, 1974- (Cambridge classical studies., 2005)
Epic games reflect the realities of epic: heroism, power and war. This first major examination of the games in Statius' Thebaid offers a new reading of the poem as a whole. General consideration is also given to the tradition of games in ancient epic, from Homer to Lucan.